Simple Fitch Proof without using DeMorgan's Law
Can someone tell me how to prove B → ¬A given the premises 1: (B ∧ A) → D and 2: (B ∧ A) → D using the Fitch system?
I have been trying to solve this proof using DeMorgan's law, but I am unable to as this proof is bound by Fitch rules (= intro, = elim, ^ into, ^ elim, etc.) -- I'll link the Fitch Rule Summary below:
https://www.ocf.berkeley.edu/~brianwc/courses/logic/rulesummary.html
I was trying to solve this proof using DeMorgan's law, Double Negation Law, Simplification Law, and MT law, but once again, I am bound by Fitch rules.
These are the premises and goal:
1: ¬(D ∨ ¬C)
2: (B ∧ A) → D
Goal: B → ¬A
Without DeMorgan law it's usually not that straightforward and you need more design for your proof search as following sketched:
B ---assume
A ---assume
B ∧ A ---∧ intro
(B ∧ A) → D ---premise
D --- → elim (MP)
D ∨ ¬C ---∨ intro
¬(D ∨ ¬C) ---premise
⊥ ---⊥ intro
¬A --- ¬ intro
B → ¬A --- → intro